Impact of SARS-CoV-2 infection on veterinary medical education - Islam, Md. Aminul; Alam, Mohammad Shah (Journal of University Teaching and Learning Practice, 2021)
SARS-CoV-2 infection is considered an international disaster. The second and third waves of the SARS-CoV-2 pandemic are ongoing. The universities of most countries of the world are closed to prevent the spread of SARS-CoV-2 infection. Many universities of the globe stopped direct classroom teaching, and some started online teaching to minimise the effects of SARS-CoV-2 on education. In this manuscript, an attempt has undertaken to analyse the influence of the SARS-CoV-2 pandemic on global veterinary medical education. We have conducted a literature search in different databases following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines using different keywords to find out peer-reviewed scientific articles about the impact of COVID-19 on veterinary medical education. The literature search generated 17 eligible scientific papers for qualitative analysis of the effect of COVID-19 on veterinary medical education. The COVID-19 pandemic has a severe adverse influence on veterinary medical education. Shifting from direct classroom teaching to online teaching is one of the sweeping impacts. It might be possible to conduct online classes for veterinary medical education. But the supply of electronic devices, motivation to students in self-learning, institutional support etc., are crucial for interactive situated learning of veterinary courses. Research and development of sustainable, worthwhile methods for remote teaching veterinary medical students are essential. Reshaping the veterinary medical education programs using core theory, practical and clinical curricula is crucial for conducting uninterrupted veterinary education programs during current COVID-19 and future pandemics.